(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the stylistic and communicative functions of syntactic devices, with a particular focus on inversion. By examining a range of illustrative examples, the paper demonstrates how inversion enhances emphasis, rhythm, and rhetorical impact in both written and spoken discourse. The analysis reveals the strategic use of inversion as a means of enriching language and reinforcing meaning, particularly in formal and persuasive contexts.